Applying the Theory of Planned Behavior to Sedentariness and Stress - Shana M. Walsh; M. Renée Umstattd Meyer; Grant B. Morgan; Rodney G. Bowden; Eva Doyle; Paul M. Gordon (New Prairie Press, 2018)
Objective: The purpose of this study was to evaluate the predictive value of the theory of planned behavior (TPB) in the sedentary behavior (SB) of young and middle-aged U.S. adults. Relationships between SB over a six-week period were examined using socio-demographic characteristics, TPB constructs, and a stress variable. Methods: Participants (n=45, mean age=31 years, 70% female, 83% White) completed surveys that included sociodemographic information, TPB constructs, and the Weekly Stress Inventory. Participants wore an activity monitor for six weeks and completed the stress inventory once weekly over the study period. A longitudinal model was estimated to determine the relationship between TPB constructs, socio-demographic characteristics, and stress level with SB across the six weeks.Results: Activity monitors revealed participants were sedentary for approximately 11 waking hours per day (SD=1.4). Bivariate analyses indicated a small effect between subjective norms and SB. Model fit indices modestly supported TPB constructs in explaining SB (i.e., a 2.3% reduction in person-level error variance); and a modest relationship between greater stress and less SB (i.e., additional 1.4% reduction in person-level error variance).Conclusions: Results cautiously support continued exploration of the TPB in SB research. Like most behaviors, the TPB alone may not fully explain SB. Future research should continue to explore theoretical determinants of SB, expand to include other theoretical models; and include diverse populations. More research is needed to understand the relationship between SB and stress. Practitioners are encouraged to consider both SB and stress in holistic efforts to improve the health of adults.